TOURISTIC WEB SITES PERFORMANCES AND GOVERNANCE TYPOLOGIES - Bianchi, Massimo; Tampieri, Laura (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2013)
The paper aims to highlight and discuss the results of the research, still in progress, about the influence of web sites governance for the touristic promotion of the territory on the criteria through which these communication channels are planned and used. To this purpose the research will compare the Private, Public and No Profit organizations web sites on the basis of two groups of performance parameters regarding, from one side, the offer of information and, from the other, the offer of services. In particular the first set of parameters is composed by: multilinguism, number of images, level of interactivity and of information up-to dating together with the facility of navigation; while the evaluation of services offer refers to online services, e-commerce, integration with the territory items and events. The main hypothesis the research aims to test is, according to the common sense, that the private governance of web sites, respect to the no profit and public one, is mostly addressed to the services than information offer. The relevance of this research topic derives from the consideration of web as a primary channel for the diffusion, processing, search and storage of information about the tourism. Another reason is the increasing resources invested by private and public bodies in the publishing and maintaining of tourism web sites that represent themselves a territory to be explored and enjoied by web tourists.